Environmental Kuznets Curve Hypothesis: An Empirical Testing (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Environmental Kuznets Curve Hypothesis: An Empirical TestingOjasviniThe Environmental Kuznets Curve (EKC) is a hypothesized relationship among various indicators of environmental degradation and income per capita. During the early stages of economic growth, degradation and pollution increase, but beyond some level of income per capita (which will vary for different indicators) the trend reverses, so that at high income levels economic growth leads to environmental improvement. This implies that the environmental impact indicator is an inverted U- shaped function of income per capita. This study tests the EKC hypothesis using the panel data framework. The analysis is based on data from a panel of 30 countries (both developing and developed nations) from the period 1985-2014. This panel data modelling involves the use of two main estimation techniques namely, fixed effects and random effects techniques. Thereafter, the research concludes by comparing the viability of both types of modelling and, highlighting out the critiques of the EKC hypothesis.